A cross-sectional investigation of factors associated with Antenatal Care Utilisation in Namibia - Heita, Saima Ndapanda (My University, 2020)
Background: Many developing countries including Namibia are far below the Sustainable Development Goals (SDG) targets. Developing countries have lower uptake of Antenatal Care (ANC) services, and therefore high rates of maternal, under-five, and neonatal mortalities. In Namibia, women of reproductive age and infants are at high risk of dying, owing to various maternal health complications. This may however be linked to lower and infrequent uptake of ANC services at healthcare facilities. The Namibian government has not adequately addressed the various factors associated with equity and accessibility to primary healthcare. For instance, women living in rural areas lack access due to travelling distances to ANC healthcare facilities, poor road infrastructure as well as poor transportation systems – in comparison to their urban counterparts. This study thus explored the different factors that may influence ANC utilisation amongst pregnant women in Namibia. Methodology: This study utilised secondary data from the 2013 Namibia Demographic and Health Survey (NDHS). A sample of 3,952 (3,819 weighted) women aged 15-49 years who had given birth in the five years prior to the survey and responded to the question on ANC utilisation were included in the study. In this study, the outcome variable was the number of ANC visits taken by women and it was a binary variable with categories “Less than 4 visits and 4+visits. The predictor variables were the predisposing and enabling factors as guided by the Anderson Healthcare Utilisation Framework as well as by literature reviewed. The Binary Logistic Regression Model (BLR) was used to explain the effects of the predictor variables on ANC utilisation. Results: More than eighty five percent(85.68%)of the sample had made at least four ANC visits and 14.33% had made less than four ANC visits during their last pregnancies. Based on the full adjusted model, predisposing factors such as maternal age, women’s parity, women’s level of education, husband/partner’s level of education, and women’s ethnicity were found to be significantly associated with ANC utilisation amongst pregnant women in Namibia. Results indicated that for every additional year of age for women in Namibia, the chances of having at least four ANC visits increased by 5.50%(OR=1.055; 95% CI: 1.027 –1.083). Another observation was an inverse relationship between ANC utilisation and the number of children born to a woman, indicating that the likelihood of attending at least four ANC sessions reduces by 11.70%(OR=0.883; 95% CI:0.804 -0.971) as parity increases. As with women’s educational attainment, the probability of having at least four ANC visits increased by 101.10% OR =2.011; 95% CI: 1.360 –2.973) for women with secondary/higher educational levels as compared to those with no education. Women whose husbands/partners attended up to secondary/higher educational levels were more likely to have at least four ANC visits by 58.80% (OR =1.588; 95% CI: 1.097 –2.299) than those whose husbands/partners had no education at all. Moreover, when compared with Damara/Nama speaking women, the odds of having at least four ANC visits increased by 85.90% (OR= 1.859; 95% CI: 1.078 –3.205) amongst Oshiwambo speaking women. However, the lowest rates of ANC utilisation were observed amongst Herero speaking women and those belonging to ‘other’ ethnic groups with 54.70% (OR= 0.453; 95% CI: 0.280 –0.732)and 44.90% (OR= 0.551; 95% CI: 0.333 –0.912) respectively. With regards to the enabling factors as outlined by the full adjusted model, health insurance was found to have a significant influence on the utilisation of ANC services by women in Namibia as women with health insurance were129.20% (OR=2.292; 95% CI: 1.406 –3.735) more likely to utilise full ANC services compared to women with no health insurance. Variables such as wealth index, residence, and regions of residence which were found to have an influence on ANC utilisation under the unadjusted, predisposing, or enabling models, were however found not to be significant under the full adjusted model. Conclusions: The overall conclusion made from this study is that ANC utilisation is still a challenge in Namibia, particularly amongst multiparous, younger and uneducated women, and residents of rural areas. In addition, ANC utilisation was observed to be low amongst women whose husbands/partners had no education. Furthermore, the regional, and ethnic differentials in ANC utilisation indicated that lower ANC utilisation was prevalent amongst residents of Central, North-eastern, and Southern regions as well as amongst Hereros and ‘other’ ethnic groups. The inference drawn from the findings is that even though the country’s National Reproductive and Child Health Policy and the National Health Policy Framework were established to address the maternal healthcare burden in the country, better strategies were not put up that would educate all women on the benefits of ANC services utilisation regardless of their socio-economic status. It is thus crucial for policymakers to scale up inclusive strategies that would enable all women in the country to fully utilise ANC services without any hindrances. Such measures should be able to eradicate all physical, economic, and socio-cultural barriers to ANC utilisation in the country